Pengaruh Gaya Belajar terhadap Tingkat Stres Siswa Sekolah Menengah Kejuruan Polimedik Depok - Siskandar, Siskandar; Mulyono, Ahmad (Cendekia: Jurnal Pendidikan dan Pembelajaran, 2021)
This study aims to determine and test empirical data related to student learning styles on stress levels. This research uses a quantitative approach through a survey method. The sample of this research was 69 students of SMK Polimedik Depok. Data were collected techniques using a questionnaire, observation, and documentary studies. The data analysis technique used is descriptive analysis, correlation coefficient, and simple regression analysis. The results of this study indicate that there is a negative and significant influence between learning styles and stress levels of students of SMK Polimedik Depok. This is known based on the results of the correlation coefficient of -0.515 and the coefficient of determination R-square of 0.265. The simple regression results show the equation Å¶ = 51.049 - 0.177 X1, which means that partially if there is an increase in one unit of learning style score, it will affect the decrease in student stress level scores by 0.177.